From health for all to universal health coverage: Alma Ata is still relevant - Kiran Raj Pandey (Globalization and Health, 2018)
Abstract With increasing adoption of universal health coverage (UHC), the health for all agenda is resurgent around the world. However, after a promising start the first time in 1978, the health for all agenda fizzled over the next decade. This commentary discusses the origin of the health for all agenda in the 1970s and the influence of global politico-economic forces in shaping that agenda, its demise and the resurgence in the form of UHC in the twenty-first century. We discuss UHC’s focus on finances and the increasing role of market economy in health care, and the opportunities and risks UHC poses. We conclude by saying that UHC’s greater focus on finances is prudent, but in order to achieve its promise, UHC needs to regulate the market based provision of healthcare, and incorporate more of the people and community centered ethos of its earlier iteration from 40 years ago.